Prevalence and clinical correlates of hyperhomocysteinemia in Chinese urban population with hypertension - Xu, Yayun; Feng, Haixing; Zhang, Liping; Li, Yanlei; Chi, Feng; Ren, Lijie (Frontiers in Endocrinology, 2024)
Context The coexistence of hypertension and elevated homocysteine (Hcy) levels has a mutually reinforcing impact on the susceptibility to cardio-cerebrovascular disease. Objective The aim was to assess the prevalence, clinical correlation, and demographic characteristics of hyperhomocysteinemia (HHcy) within the Chinese urban population with hypertension. Methods A cohort of 473 individuals with hypertension were selected from four communities in Shenzhen, China. Demographic attributes, clinical profiles, and lifestyle behaviors were gathered and compared between individuals with and without HHcy. A logistic regression model was employed to examine potential factors associated with the prevalence of HHcy. Correlation between Hcy levels and clinical characteristics was assessed through multiple linear regression analysis. Results The prevalence of HHcy in the population with hypertension was 31.3%. In comparison to individuals without HHcy, those with HHcy exhibited a higher proportion of males, a higher prevalence of smoking and alcohol consumption, and a higher proportion of cases with the homozygous (TT) genotype at the MTHFR C677T polymorphism. Moreover, individuals with HHcy had lower levels of folic acid (FA), and lower fruit and vitamin B12 intake. Furthermore, the risk factors for HHcy were male (B = 1.430, OR = 4.179) and MTHFR (TT) (B = 1.086, OR = 2.961). In addition, the multiple linear regression analysis revealed a significant association between Hcy levels and gender (B = -2.784, P = 0.004), MTHFR genotypes (B = 1.410, P = 0.005), and FA levels (B = -0.136, P = 0.030). Conclusion The high prevalence of HHcy among hypertensive patients in this Chinese urban population underscores the necessity for interventions targeting modifiable risk factors such as dietary choices and lifestyle practices.